The Effect of Pec Deck Flyes and Cable Crossover Exercises on Arm Muscle Strength and Tennis Forehand - Maulidin, Maulidin; Summinar, Tiassari Janjang; Syariofeddin, Elya Wibawa (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The purpose of this study was to determine the effect of Pec Deck Flyes and Cable Crossover training on Arm Muscle Strength and Forehand in male tennis players. This type of research is an experimental study using